Exact Periodic Solutions of the Nonintegrable Kawahara Equation. (23rd August 2012) - Kamenov, Ognyan Yordanov; Angova, Anna P.
Abstract : In the present paper, we have obtained an exact biperiodic, one-phase solution of the Kawahara evolution equation. Two classes of real periodic waves generated by the biperiodic solution have been analyzed. A modification of the bilinear-transformation method has been applied allowing to provide a single solution of the residual equation derived from the bidifferential reduction of the considered nonintegrable equation. It is shown that the spatial displacements are individual for each separate harmonic of the real periodic solutions.